On the origin of 'fuzz' formation in plasma-facing materials. (9th July 2019) - Dasgupta, Dwaipayan; Kolasinski, Robert D.; Friddle, Raymond W.; Du, Lin; Maroudas, Dimitrios; Wirth, Brian D.
Abstract: Tungsten, the material used in the plasma-facing components (PFCs) of nuclear fusion reactors, develops a fuzz-like surface morphology under typical reactor operating conditions. This fragile 'fuzz' surface nanostructure adversely affects reactor performance and operation. Developing predictive models, capable of simulating the spatiotemporal scales relevant to the fuzz formation process is essential for understanding the growth of such extremely complex surface features and improving PFC and reactor performance. Here, we report the development of an atomistically-informed, continuous-domain model for the onset of fuzz formation in helium plasma-irradiated tungsten and validate the model by comparing its predictions with measurements from carefully designed experiments. Our study demonstrates that fuzz forms in response to stress induced in the near-surface region of PFCs as a result of plasma exposure and helium gas implantation. Our model sets the stage for detailed descriptions of this complex fuzz formation phenomenon and similar phenomena observed in other materials.